PENGARUH LATIHAN MEDITASI DENGAN TINGKAT KECEMASAN PERAWAT YANG BERTUGAS DI RUANG ISOLASI COVID-19 RUMKIT TK. II UDAYANA - I Made Artaguna; Ni Made Ari Sukmandari (STIKES ADVAITA MEDIKA TABANAN, 2022)
Nurses as the front line in handling COVID-19 are at risk of experiencing anxiety disorders due to the increasing workload, worrying about their health, and that of their families. Meditation is an attempt to improve stress conditions and eliminate psychosocial problems. This study aims to determine the effect of meditation practice on the anxiety level of nurses on duty in the COVID-19 Isolation Room of Rumkit Tk. II Udayana. This study used a pre-experimental method with a One group pre-test-posttest design. This study involved 23 samples selected by purposive sampling technique. Collecting data using the Hamilton Anxiety Rating Scale, meditation is given for 15 minutes every day for a week. Data analysis consists of data analysis using paired t-test. The test results showed that the average pre-test anxiety was 23.96 and the post-test was 9.65. The results of the Paired t Test showed that the t value = 19.200 > 2.069 and the p value 0.001 < 0.05 indicating there was a significant difference in the level of anxiety of nurses before and after doing meditation. Isolation. It is recommended to hospitals to use meditation practice as a collaboration in order to reduce anxiety levels and it is necessary to increase promotion so that the management of anxiety levels using meditation exercises is increasingly known to the public.